2002
DOI: 10.5194/angeo-20-757-2002
|View full text |Cite
|
Sign up to set email alerts
|

On the incidence of Kelvin-Helmholtz instability for mass exchange process at the Earth’s magnetopause

Abstract: Abstract. Due to the velocity shear imposed by the solar wind flowing around the magnetosphere, the magnetopause flanks are preferred regions for the development of a KelvinHelmholtz instability. Since its efficiency for momentum transfer across the magnetopause has already been established, we investigate its efficiency for mass transfer. Using nonresistive magnetohydrodynamic simulations to describe the magnetic field shape in the instability region, we use testparticle calculations to analyse particle dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…However, solar wind pressure pulses and KH or TBL waves cannot explain the flows in GSE Y‐direction or the observed ion dispersion. It does not seem that these mechanisms are able to explain significant transport of plasma (especially electrons) into the MS [ Smets et al , 2002]. Thus once more we cannot exclude that indentation of the MP can be caused by one of these mechanisms, though we still would need reconnection to explain other observed features.…”
Section: Discussionmentioning
confidence: 98%
“…However, solar wind pressure pulses and KH or TBL waves cannot explain the flows in GSE Y‐direction or the observed ion dispersion. It does not seem that these mechanisms are able to explain significant transport of plasma (especially electrons) into the MS [ Smets et al , 2002]. Thus once more we cannot exclude that indentation of the MP can be caused by one of these mechanisms, though we still would need reconnection to explain other observed features.…”
Section: Discussionmentioning
confidence: 98%
“…However, they do not spatially resolve the reconnection boundaries yet. Other MHD simulations have examined the acceleration of O + test particles in the presence of an KH instability developing at the MP (Smets et al, 2002), but without taking them into account self-consistently. Because all these MP physical processes have a significant impact on macroscopic scales, incorporating the effect of the O + component on such MP processes would be an important challenge.…”
Section: Discussionmentioning
confidence: 99%
“…An analytical expression of this instability threshold can be obtained for an ideal MHD plasma in an incompressible media (e.g. Smets et al 2002). It can also be demonstrated that, in the incompressible media approximation, the component of the instability wave vector perpendicular to the interface is purely imaginary.…”
Section: Khi Before the Cluster And Themis Eramentioning
confidence: 99%